Vienne Aujourd'hui. - Meisl, F. Thomas (Toulon : Musée de Toulon, 1990)
Anzinger, Siegfried ; Attersee, Christian Ludwig ; Brandl, Herbert ; Damisch, Günter ; Graf, Franz ; Kern, Josef ; Kienzer, Michael ; Kocherscheidt, Kurt Kappa ; Mosbacher, Alois ; Oberhuber, Oswald ; Rainer, Arnulf ; Rockenschaub, Gerhard ; Schlegel, Eva ; Schmalix, Hubert ; West, Franz ; Wölzl, Rainer ; Wurm, Erwin ; Zechner, Johannes ; Zogmayer, Leo
Vienne Aujourd'hui, Musée de Toulon, 10 juillet - 31 octobre 1990
Frans
kunstcatalogus
Keywords: Oostenrijk; Wenen